Research on Applications of Transurethral Plasmakinetic Enucleation of the Prostate in Elderly Patients Aged ≥80 Years - Su, Wen; Yi, Ye; Zeng, Liang; Tang, Jin (Frontiers in Surgery, 2021)
Objective: To evaluate the safety and efficacy of transurethral plasmakinetic enucleation of the prostate (PKERP) vs. transurethral resection of the prostate (TURP) in elderly patients aged ≥80 years with benign prostate hyperplasia. Materials and Methods: We conducted a retrospective analysis of the PKERP (n = 123) and TURP (n = 143) in patients aged ≥80 years at urology department of The Third Xiangya Hospital of Central South University from January 2016 to October 2019. Then the preoperative, intraoperative, and postoperative data of different indicators were compared between the two groups. The follow-up was done at 3 months, 1 year after surgical treatment. Results: No significant differences were observed between the two groups for the baseline characteristics, including age, prostate volume, prostate-specific antigen (PSA) level, concurrent disease, maximum urinary flow rate (MFR), international prostate symptoms score (IPSS), and quality of life (QoL) score. The operative time, hemoglobin decrease, and postoperative flushing time were significantly lower in the PKERP group compared with the TURP group. However, no significant differences were observed between both groups for postoperative hospital stay, incidence of transurethral resection syndrome (TURS), prostatic capsular perforation, and genuine urinary incontinence. The follow-up results showed that the MFR of the PKERP group was significantly higher than the TURP group at 1 year after surgery. Conclusion: Compared with TURP, PKERP is a safe and efficacious method for treating patients aged ≥80 years with benign prostate hyperplasia, and it may improve long-term urination symptoms.